Intra- and inter-annual variations in Chironomidae (Insecta: Diptera) communities in subtropical streams - Diane Nava; Rozane M. Restello; Luiz U. Hepp (Zoologia (Curitiba), 2015)
The structure and composition of stream benthic communities are strongly influenced by spatial and temporal factors. This study evaluated the intra and inter-annual variations in Chironomidae communities in subtropical streams. The organisms were sampled from 10 small-order streams during the summer and winter of 2010-2012. The number of chironomid specimens sampled was 7,568, distributed in 49 genera. Chironomid abundance and richness varied intra and inter-annually and community composition varied intra-annually (2010 and 2011). Water temperature, total organic carbon, nitrogen, and rainfall were correlated with chironomid community composition. The intra-annual variation of the community was dependent on climatic variations (temperature and rainfall) and changes caused by intensive agricultural use. We conclude that the temporal variation observed in the Chironomidae community correlates with climatic variations (rainfall) and changes in the total organic carbon and total nitrogen, caused by intensive agricultural land use.